Performance of DSSS Signal Transmission with SCM over Low-Frequency MMF Passbands - Patmanee, Jaruwat; Kanprachar, Surachet (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2022)
The transmission of a high data rate signal over low-frequency passbands of multimode fibers is studied in this paper. The subcarrier multiplexing (SCM) technique is applied to mitigate the frequency-selective nature of the passbands, at which many nulls can degrade the signal transmission. The subcarrier frequencies must be chosen appropriately, especially for some low-frequency passbands; otherwise, poorly received subcarrier signals will be obtained, affecting the entire transmission. Rather than transmitting many subcarrier signals over these passbands, the direct sequence spread spectrum (DSSS) technique can be adopted. In this work, a high data rate signal is transmitted over 1 km of multimode fiber using the 3-dB modal band and six other low-frequency passbands. The signal is separated into four sub-signals transmitted over four different channels: the 3-dB modal band, two low-frequency passbands, and one passband (containing four low-frequency passbands). In the last passband, the sub-signal is transmitted using the DSSS, while the other sub-signals are transmitted through amplitude shift keying (ASK) modulation. The performance of the system is determined using the bit error rate (BER). The findings reveal that by applying the DSSS to some low-frequency passbands, robustness is obtained in the subcarrier frequency for use in the DSSS passband. A BER lower than 10-9 with a total data rate of 600 Mbps is achieved. This data rate is three times higher than the data rate obtained by the 3-dB modal band. This performance is achieved without applying any error-correction code.